Gene Editing: A New Era in Medicine, Agriculture, and Ethics - Jadhav, Aarya Mahesh (International Journal of Engineering and Management Research, 2025)
Gene editing projects to a set of technologies that allow worldwide scientists to make corrections and changes in the DNA of a living organism. This ability correctly modifies genes in advanced fields like medicine and agriculture. In medicine, it finds out possibilities for curing genetic disorders, while on the other hand in farming practices, it holds credit for creating genetically modified crops that are more resistant to various diseases and environmental stresses. However, the ethical challenges on the society of gene editing remain a sign of concern, raising concerns about its potential misuse. This paper finds out the applications, capacity and logical considerations surrounding gene editing, with a focus on its impact in India.